فاعلیة إستراتیجیة التعلم التعاونی فی تدریس مقرر الفهرسة الوصفیة وأثرها على التحصیل الأکادیمی وتکوین الاتجاه نحو المقرر لدى طلاب المکتبات والمعلومات - د. علاء عبد الستار مغاورى (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aims to know the effect of the use of cooperative learning strategyas one of the most important active learning Strategies - which is one of therecent trends in the educational strategies - in the practical application of thepreparation of the descriptive Cataloging cards , on academic achievement andthe trend towards Course the planned study on first year students , libraries,documentation and information science Department, Faculty of Arts, DamiettaUniversity and to achieve the objectives of the study were to rely on a theexperimental method and the use many tools as Description Course, preparationof a measure of the tendency towards descriptive cataloging Course , andachievement test in the same unit , has been testing the application and scaletribal and Uday results on the experimental group and the control group of thestudy , the results indicated the presence of statistically significant differences infavor of the post application of the strategy of cooperative learning in academicachievement development and the formation of the trend towards the Course